2011
DOI: 10.1007/s00384-011-1186-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted ileal pouch-rectal muscle sheath anastomosis for the treatment of familial adenomatous polyposis

Abstract: Ileal pouch-rectal muscle sheath anastomosis is associated with better anal function than ileal pouch-anal anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Surgery is still the therapy of choice for the prevention of colonic and rectal cancer in patients with FAP, but is also considered to be one of the major risk factors for development of DTs. Moreover, surgery is currently the only known risk factor that is modifiable, and several studies have reported on routine laparoscopic total colectomy in patients with FAP.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is still the therapy of choice for the prevention of colonic and rectal cancer in patients with FAP, but is also considered to be one of the major risk factors for development of DTs. Moreover, surgery is currently the only known risk factor that is modifiable, and several studies have reported on routine laparoscopic total colectomy in patients with FAP.…”
Section: Discussionmentioning
confidence: 99%